The Particle Jako (“Like”) in Spoken Czech: From Expressing Comparison to Mobilizing Affiliative Responses - Oloff, Florence (Frontiers in Psychology, 2022)
This contribution investigates the use of the Czech particle jako (“like”/“as”) in naturally occurring conversations. Inspired by interactional research on unfinished or suspended utterances and on turn-final conjunctions and particles, the analysis aims to trace the possible development of jako from a conjunction to a tag-like particle that can be exploited for mobilizing affiliative responses. Traditionally, jako has been described as a conjunction used for comparing two elements, or for providing a specification of a first element (“X (is) like Y”). In spoken Czech, however, jako can be flexibly positioned within a speaking turn and does not seem to operate as a coordinating or hypotactic conjunction. As a result, prior studies have described jako as a polyfunctional particle. This article will try to shed light on the meaning of jako in spoken discourse by focusing on its apparent fuzzy or “filler” uses, i.e., when it is found in mid-turn position in multi-unit turns and in the immediate vicinity of hesitations, pauses, and turn suspensions. Based on examples from mundane, video-recorded conversations and on a sequential, multimodal approach to social interaction, the analyses will first show that jako frequently frames discursive objects that co-participants should respond to. By using jako before a pause and concurrently adopting specific embodied displays, participants can more explicitly seek to mobilize responsive action. Moreover, as jako tends to cluster in multi-unit turns involving the formulation of subjective experience or stance, it can be shown to be specifically designed for mobilizing affiliative responses. Finally, it will be argued that the potential of jako to open up interactive turn spaces can be linked to the fundamental comparative semantics of the original conjunction.